Potensi dan Produktivitas Kolang Kaling dalam Perkembangan Ekonomi Masyarakat di Kampung Lamkareung Kecamatan Indrapuri Kabupaten Aceh Besar (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Lamkareung Village is a village located in Indrapuri District, Aceh Besar Regency. There are several commodities produced by Lamkareung Village, including fruit and fronds. Based on the discussion with the service team, the fruit palm fruit will be processed because it is easy to process and the consumers can come from various groups. The Head of Lam Kareung Village hopes that the fruit fruit fruit commodity can increase its selling value, and increase income for residents. It can also become a typical food of LamKareung village. The partners accompanied were representatives of village officials. This was done on the advice of the Head of LamKareung village because it was considered that these women were cadres and representatives who would later be able to pass on the knowledge gained to other residents. This service focuses on helping residents make processed palm fruit in the form of natural coloring crackers. As a result of the assistance and training carried out by the team, residents can make candied fruit and fronds with natural colors and use a cutting machine.